Penggunaan Media Kahoot Dalam Pembelajaran IPS untuk Meningkatkan Minat Belajar Siswa Kelas IV SDN 16 Padang Magek - Saskia Aulia Putri; Rio Armanda; Salsabila Aryunda Fitri; Selvi Amanda Putri; Susi Ratna Sari (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2026)
This study aims to improve the learning interest of fourth-grade students at SDN 16 Padang Magek in Social Studies (IPS) through the use of Kahoot, a digital game-based learning platform. The background of this research stems from the low enthusiasm of students in IPS classes, which were often monotonous and focused on memorization. To address this issue, Classroom Action Research (CAR) was conducted using the Kemmis & McTaggart model, consisting of four stages: planning, action, observation, and reflection. The research was carried out collaboratively between the researchers and the classroom teacher, employing a qualitative approach. Data were collected through observation sheets, field notes, and documentation, then analyzed descriptively to capture the dynamics of student engagement. The findings reveal that Kahoot successfully created a more interactive, enjoyable, and competitive learning environment. Students who were previously passive became more enthusiastic, confident, and actively participated in answering questions. Kahoot also strengthened teacher–student interaction, with teachers acting as facilitators during the quiz sessions. Both individual and team modes encouraged students to develop social skills such as cooperation, communication, and responsibility. Thus, Kahoot functioned not only as an evaluation tool but also as a medium to foster intrinsic motivation and meaningful learning experiences. Overall, this research confirms that innovative educational technology like Kahoot can serve as a practical strategy for teachers to enhance the quality of Social Studies learning in elementary schools. Kahoot proved effective in increasing student interest, supporting social skill development, and preparing a technologically literate generation ready to face global challenges.